Impact of Working Capital Management on Profitability of the Selected Listed FMCG Companies in India - Jana, Debabrata (Universitas Prasetiya Mulya, 2018)
Working capital management plays a vital role in the success of businesses because of its effect on profitability and liquidity. The purpose of this study is to examine the relationship and the efficiency of the working capital management strategies of FMCG Company in India. The study used secondary data collected from all the fifteen listed FMCG Company covering the period from 2013-2017. Using panel data analysis, the study finds a significantly positive and negative relationship between profitability and working capital management. Therefore, efficient management of working capital for FMCG Company not only has a positive relationship with profitability but significantly impacts on such firm’s profitability.